Sage in Jewish Society of Late Antiquity. - Kalmin, Richard (Routledge, 1998)
The Sage in Jewish Society of Late Antiquity provides an erudite and stimulating analysis of the role of the sage in late antiquity and sheds new light on rabbinic comments on diverse topics such as biblical heroes and genealogy and lineage.